Keanekaragaman Jenis Belalang (Orthoptera) di Kawasan Universitas Negeri Padang Kampus Air Tawar Barat - Mustika, Niken; Azzahrianto, Octavia Putri; Syamsurizal (Bioconsortium : Biological Research and Education, 2025)
Grasshoppers (Orthoptera) are insects commonly found in various terrestrial habitats and play an important role in ecosystems. This study aims to investigate the species diversity of grasshoppers in the University of Padang Air Tawar Barat Campus area. The methods used include visual surveys conducted in the morning and evening, with specimen collection in gardens and open fields. Specimens were collected, preserved, and identified morphologically, and analyzed using the Shannon-Wiener index. The results showed the presence of 6 species from 3 families and 5 subfamilies. The diversity index values indicated a fairly even species distribution (E’ = 0.8192) and medium species richness (Dmg = 2.085). These findings reflect the campus ecosystem’s continued support for the presence of various Orthoptera species and highlight the importance of preserving their conservation.